Antibacterial and analgesic activity of leaves of Lantana camara - L. Kalyani,; A. Lakshmana Rao,; U.S. Mishra, (International Journal of Phytomedicine, 2011)
The leaves of the plant Lantana camara were extracted with different solvents and screened for their antibacterial and analgesic activities. The chloroform and methanolic extract of the plant Lantana camara has showed the presence of four alkaloid compounds each. Antibacterial activity was evaluated using MIC method against bacteria. The analgesic activity of different extracts of Lantana camara leaves is evaluated by Eddy’s hot plate method where the responses are jumping withdrawal of paws and licking of paws. This study demonstrates that leaf powder of Lantana camara has significant antibacterial and analgesic activities.